'The Good Wife' : a phenomenological re-reading of Proverbs 31:10-31 in the context of HIV / Aids in Zimbabwe - Chitando, Ezra (Scriptura : Journal for Biblical, Theological and Contextual Hermeneutics, 2004)
HIV / AIDS poses a serious existential challenge in Africa. Its effects have been devastating, particularly for the disadvantaged members of society. Women, children, orphans, displaced people, prisoners and others have been negatively affected by the pandemic. Patriarchy has also compounded the vulnerability of women. Women are unable to negotiate safer sexual practices with their partners, especially in the marriage context. Religious and cultural factors have combined to dangerously expose women to HIV infection in Africa. Due to the influence of Christianity in Africa, its sacred writings have been used selectively to justify the marginalisation of women. This study offers a re-reading of Proverbs 31: 10-31. It interrogates the meaning of being "the good wife" in the context of HIV / AIDS in Zimbabwe. The first section analyses the influence of African and biblical patriarchal values and how they expose women to HIV infection. The second section explores new models for appreciating "the good wife" in the era of HIV / AIDS. The third section calls for greater action by women's religious groups in HIV / AIDS awareness, prevention and care. Phenomenological techniques like cultivating empathy and recognising the value of religion guide the study.
Free